Examining Malay Customary Marriage Law in the Malay Countries: An 'Urf Perspective - Asrizal Saiin; Mohamad Azmi Karuok; Moh. Zaidi Hajazi; Anwar M. Radiamoda (Hukum Keluarga Islam IAIN LANGSA, 2023)
The purpose of this paper is to find out more clearly about the position of customary law for the Malay community, which can be said to be all Muslim, by analyzing it through the study of ‘urf in Islamic law. This research is categorized as qualitative research. Qualitative research intends to understand the phenomenon of what is experienced by the research subject, for example, behavior, perception, motivation, action, and others, thoroughly and descriptively in a special natural context by utilizing the scientific method. The findings in this paper are that Malay customary marriage law, which has been practiced so far in Malay countries, is in accordance with Islamic law. The Malay customary marriage law that may be applied is a law that does not conflict with Islamic values, or 'urf al-sahih. Meanwhile, Malay customary marriage law that cannot be applied is a law that is contrary to Islamic values, or 'urf al-fasid, because it can damage the purpose of the shari'a to be passed down (maqashid shari'ah).